Reading for understanding : toward an R & D program in reading comprehension - Snow, Catherine E. (RAND education., 2002)
In fall 1999, the Department of Education's Office of Educational Research and Improvement (OERI) asked RAND to examine how OERI might improve the quality and relevance of the education research it funds. The RAND Reading Study Group (RRSG) was charged with developing a research framework to address the most pressing issues in literacy. RRSG focused on reading comprehension wherein the highest priorities for research are: (1) Instruction: How can we best promote the development of proficient reading and prevent reading comprehension difficulties? (2) Teacher preparation and professional development: How can we prepare teachers to deliver effective comprehension instruction? (3) Assessment: How can we develop an assessment system for reading comprehension that includes the design of valid and reliable measures of self-regulated, strategic reading that are sensitive to instructional interventions? RRSG concluded that the research infrastructure must: (a) obtain long-term funding that is sustained across administrations and political constituencies; (b) acquire intellectual leadership that endures over a substantial time frame and is insulated from political forces; (c) synthesize knowledge across the various research initiatives in systematic ways; (d) enlist a cadre of well-trained investigators; and, (e) fund research that is rigorous and of high quality.